1995
DOI: 10.1128/iai.63.5.1710-1717.1995
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a low-molecular-mass T-cell antigen secreted by Mycobacterium tuberculosis

Abstract: A novel immunogenic antigen, the 6-kDa early secretory antigenic target (ESAT-6), from short-term culture filtrates of Mycobacterium tuberculosis was purified by hydrophobic interaction chromatography and anionexchange chromatography by use of fast protein liquid chromatography. The antigen focused at two different pIs of 4.0 and 4.5 during isoelectric focusing, and each of these components separated into three spots ranging from 4 to 6 kDa during two-dimensional sodium dodecyl sulfate-polyacrylamide gel elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
218
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(230 citation statements)
references
References 31 publications
9
218
0
3
Order By: Relevance
“…tuberculosis and BCG, including the Myco. tuberculosis 38-kD [24], MPB70 [25] and the 10-kD ESAT-6 proteins [26]. A combination of these Myco.…”
Section: Discussionmentioning
confidence: 99%
“…tuberculosis and BCG, including the Myco. tuberculosis 38-kD [24], MPB70 [25] and the 10-kD ESAT-6 proteins [26]. A combination of these Myco.…”
Section: Discussionmentioning
confidence: 99%
“…The 6-kDa early-secreted antigenic target (ESAT-6) and culture filtrate protein 10 (CFP10) are antigens preferentially found in Mycobacterium tuberculosis and virulent Mycobacterium bovis, but not in M. bovis bacille Calmette-Guérin vaccine or most environmental mycobacteria [20][21][22]. It has been shown that ESAT-6 and CFP10 can stimulate peripheral blood mononuclear cells (PBMCs) from patients with tuberculosis to secrete specific IFN-c. An ex vivo enzyme-linked immunospot (ELISPOT) test employing these antigens and detecting IFN-csecreting T-cells in peripheral blood [23][24][25][26][27] and bronchoalveolar lavage fluid [28] has been found useful in diagnosing latent and active tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that ESAT-6, CFP-10 and/or ESAT-6/CFP-10, alone or in combination with other proteins or BCG, induce strong protective T cell immunity during Mtb infection, especially in a murine model of TB [11,13,14,[27][28][29]. These reports have led to extensive research to realize the potential of these proteins as vaccine candidates [29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%